(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
Guidance is a key discipline in the comprehensive development of individuals, covering educational, professional, family, vocational, and personal-social areas. This study analyzes research trends in Latin America from 2018 to 2023. A methodology based on a systematic literature review was used, following the PRISMA protocol and consulting academic databases. The results indicate a growing interest in the field, with an increase in publications, although there was a slight decline in the last year analyzed. The most researched areas include educational, labor, and personal-social guidance. It is concluded that the diversity of studies reflects the complexity of the discipline, highlighting the importance of continuing research to strengthen both its theory and practice.